Accurate Water Quality Sampling Improves Process Controls. Issue 5 (1st May 2016) - Martin, Barb; Lichtenberg, Traci
Abstract : Water quality is key to public health, and sampling is essential to ensuring reliable, accurate water quality data to optimize water treatment plant and distribution system performance.